Pelo reconhecimento de uma entidade familiar: união homoafetiva - Bertoncini, Carla (2011)
The present thesis main message is the same-sex union recognition as a regular family entity in similarity with any other relationship committed by the affection, as well as the recognition of this union by a general clause of a fully affection union; validate the study on the family evolution and emphasize its social importance. To analyze the family in the Brazilian law and show the link between a contemporary family and a same-sex marriage family. Highlight was given to the religious and historical aspects of same-sex unions. What the Bible really says about same-sex unions. It was pointed that the same-sex unions context in the compared law and the several manners of evaluating the same-sex union. Privacy, intimacy, the exercise of ones sexuality and same-sex unions were analyzed. This study seeks, without stressing out the subject, recognize the same-sex unions as a family entity, once the Federal Constitution of 1988, by rule, did not recognized such marriages. The doctrinal and the Brazilian justice have found some fundamentals for its recognition